Balanço de energia e avaliação heurística de parâmetros de absorção de um sistema solar fototérmico baseado no nanofluido dióxido de titânio-água deionizada - Santos, Rogério Feliciano de Moura (2019)
Direct solar absorption based on nanoparticles is a technology that has shown promise for systems that use energy as useful heat. This work investigated the behavior of temperature profiles of four concentrations (12.5 ppm, 25 ppm, 50 ppm, 75 ppm) of titanium dioxide nanoparticles dispersed in deionized water in a direct sunlight absorption system. The energy balance of the system was developed to analyze the heat transfer processes involved. In addition, the computational meta-heuristic method of Harmonic Search was used to find the optical properties of the fluid absorptance and soil albedo. Test system consists of aluminum profiles and contains two glass test cells. The experiments were carried out during the period between October and December of 2018, from 06:00 to 18:00 hours. In each cell were inserted three thermocouples for to measure the temperature. Furthermore, another thermocouple was placed on the outside of the structure for measuring ambient temperature data. Data from solar radiation and wind speed were monitored by pyranometers and anemometer. The nanoparticles were dispersed by ultrasonic stirring. Data were selected from two different sky conditions for analysis: clear sky and cloudy sky. On days of clear sky two peaks and one valley were observed in the temperature profiles, the concentration of 50 ppm reached the highest temperature value of 47.2 ºC, with a temperature increase of 6.2% over that of the cell containing only water at the first observed hour. The convection between the air and the surface of the glass, directed by the wind speed, was the process that governed the thermal loss, according to the energy balance. A Pearson correlation coefficient of 0.73 was obtained between the values measured experimentally and those simulated by the Harmonic Search metaheuristic method for the system enthalpy change. In addition, Harmonic Search found similar behavior, both in the morning and in the afternoon, in the absorptance profile related to the direct radiation plot, under conditions of high incident radiation, low thermal loss and angle of solar inclination in the range between 45º and 75º. The other absorptances and soil albedo showed behavioral changes due to the probable momentary changes in the sky condition and the local topography, respectively.